SELECTION OF THE LEVELER TYPE AND JUSTIFICATION OF ITS MAIN DIMENSIONS WHEN WORKING ON SMALL CONTURAL AREAS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In the article, due to the low efficiency of existing land leveling machines in small-contour cultivated areas (up to 3 hectares), the results of choosing an effective leveling machine(П-2,8А, П-4, ПА-3 and  ППА -3,1 and others)  and justifying its main dimensions are presented. The advantages and disadvantages of the selected PU-14 ground leveler are identified. As a result of the research, a ground leveler with an improved surface, which differs from the existing leveler in terms of leveling technology (smoothing at the same time as cutting the soil layer by layer), quality of work and less effort, was created. It is based on the optimal dimensions of the ground leveler with improved roof. Using the improved leveler in small areas increases productivity by 1.6 times compared to the existing leveler, reduces power consumption by 1...7%